Kinect hacks - St. Jean, Jared; Safari eBooks (Sebastopol, CA : O'Reilly Media, 2012)
"Set up a development environment in Windows, Mac OS X, or Linux; build special effects apps with tools such as Synapse and Cinder; create gestural interfaces to integrate and control digital music components; capture the realistic motions of a 3D model with NI mate, Blender, and Animata; design gesture-based games with the ZigFu SDK; recreate the dimensions of any room in real time, using RGBDemo; use gestures to navigate robots and control PC interfaces"--P. [4] of cover.
Description based on print version record.
"Tips & tools for motion and pattern detection"--Cover.
"Make: makezine.com"--Cover.
Includes index.
Keywords: Pattern recognition systems; Multimodal user interfaces (Computer systems); Computer vision; Computer games -- Programming; Computer games -- Design; Computer input-output equipment -- Programming; Electronic books